FEMALE STUDENTS’ PERCEPTION ON BREAST CANCER DETECTION USING BREAST SELF-EXAMINANTION (SADARI) METHOD - Aulia Rahman Tanjung; Ella Nurlaella Hadi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: In Indonesia, breast cancer takes second place after cervical cancer with estimated 61,682 cases. According to International Agency for Research on Cancer (IARC) data in 2012, breast cancer was found to be the highest percentage of new cases, amounting approximately 43.3% and the death percentage caused by breast cancer reached 12.9%. Based on Basic Health Research data of 2013, the prevalence of breast cancer in Indonesia reaches 0.5 per 1,000 women. The objective of this research was to find out about teenage female students’ perception about early detection of breast cancer with SADARI method (Breast Self-Examination). Methods: This research employed qualitative research method with the phenomenological approach by using. Results: Based on the research results, there were different perceptions on the importance of conducting SADARI for teens. There were some obstacles to do SADARI such as feeling embarrassed, not having enough time to do SADARI, being forgetful, lacking information about SADARI and lacking support from family and closest people around them. Conclusions: Teenager perceptions about SADARI affect behavior to do breast self-examination. The solution to overcoming those obstacles included collecting information about early detection of breast cancer using SADARI method, learning about it, and visiting the nearest health facility to do SADARI. In addition, there must be external support from family or other closest relatives.